2011
DOI: 10.1021/jm200815w
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoramidate ProTides of the Anticancer Agent FUDR Successfully Deliver the Preformed Bioactive Monophosphate in Cells and Confer Advantage over the Parent Nucleoside

Abstract: The fluorinated pyrimidine family of nucleosides continues to represent major current chemotherapeutic agents for treating solid tumors. We herein report their phosphate prodrugs, ProTides, as promising new derivatives, which partially bypass the dependence of the current drugs on active transport and nucleoside kinase-mediated activation. They are also resistant to metabolic deactivation by phosphorolytic enzymes. We report 39 ProTides of the fluorinated pyrimidine FUDR with variation in the aryl, ester, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 26 publications
(58 reference statements)
1
118
0
Order By: Relevance
“…In some cases, they both provide similar yields like in the case of 2′- C -methyl-2-amino-6-substituted-purine ribonucleoside analogs 183 and 5-FdU (Scheme 105). 184 …”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…In some cases, they both provide similar yields like in the case of 2′- C -methyl-2-amino-6-substituted-purine ribonucleoside analogs 183 and 5-FdU (Scheme 105). 184 …”
Section: Nucleoside Monophosphate Prodrugsmentioning
confidence: 99%
“…Simple phenyl esters may well be the most extensively employed substructure [130,131], especially in nucleotide analogues such of the general structure 62 [116,127,132136]. However in cases such as the hydroxamic acid 63, an inhibitor of 6-phosphogluconate dehydrogenase for use in trypanosomiasis, addition of simple substituents such as methyl groups to the phenyl ring has resulted in more than a 10-fold increase in potency [137].…”
Section: Amidate Prodrugsmentioning
confidence: 99%
“…Delivery of the free 5'-monophosphate form of a nucleoside analogue inside a cell is particularly important as the first phosphorylation is considered as the rate-limiting step in the activation of most nucleoside analogues. The application of the 5'-phosphoramidate approach to FdUrd (2) led to the discovery and further clinical development of L-alanine-based 5'-ProTide NUC-3373 (55) [35]. Preclinical in vitro data has shown that NUC-3373 exerts its cytostatic activity independently of thymidine kinase in TK-deficient cell lines.…”
Section: -Fluorouracil and Prodrugsmentioning
confidence: 99%